Alterations in Leg Extensor Muscle-Tendon Unit Biomechanical Properties With Ageing and Mechanical Loading - McCrum, Christopher; Leow, Pamela; Epro, Gaspar; König, Matthias; Meijer, Kenneth; Karamanidis, Kiros (Frontiers in Physiology, 2018)
Tendons transfer forces produced by muscle to the skeletal system and can therefore have a large influence on movement effectiveness and safety. Tendons are mechanosensitive, meaning that they adapt their material, morphological and hence their mechanical properties in response to mechanical loading. Therefore, unloading due to immobilization or inactivity could lead to changes in tendon mechanical properties. Additionally, ageing may influence tendon biomechanical properties directly, as a result of biological changes in the tendon, and indirectly, due to reduced muscle strength and physical activity. This review aimed to examine age-related differences in human leg extensor (triceps surae and quadriceps femoris) muscle-tendon unit biomechanical properties. Additionally, this review aimed to assess if, and to what extent mechanical loading interventions could counteract these changes in older adults. There appear to be consistent reductions in human triceps surae and quadriceps femoris muscle strength, accompanied by similar reductions in tendon stiffness and elastic modulus with ageing, whereas the effect on tendon cross sectional area is unclear. Therefore, the observed age-related changes in tendon stiffness are predominantly due to changes in tendon material rather than size with age. However, human tendons appear to retain their mechanosensitivity with age, as intervention studies report alterations in tendon biomechanical properties in older adults of similar magnitudes to younger adults over 12-14 weeks of training. Interventions should implement tendon strains corresponding to high mechanical loads (i.e. 80-90% MVC) with repetitive loading for up to 3-4 months to successfully counteract age-related changes in leg extensor muscle-tendon unit biomechanical properties.